Britain, détente, and changing East-West relations - White, Brian, 1947- (London ; New York : Routledge, 1992)
Argues that Britain's contribution to East-West detente has been consistently undervalued. Re-evaluates Britain's role in the post-war world and provides a valuable case study in foreign policy formulation and implementation.
Book Cover; Title; Contents; Acknowledgements; Introduction; The concept of detente; Britain, the cold war and detente; Britain as a catalyst of detente; Britain and the Partial Test Ban Treaty; The decline of British influence on East-West relations; Britain, the new cold war and detente; A British conception of detente; Conclusion; Notes; Bibliography; Index.
Includes bibliographical references (pages 191-198) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: World politics -- 1945-1989.; East and West; Detente; Great Britain -- Foreign relations -- 1945-; Politique mondiale -- 1945-1989.; Détente (Politique); Grande-Bretagne -- Relations extérieures -- 1945-; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; Detente; East and West; Diplomatic relations; World politics; Great Britain; Ost-West-Konflikt; Geschichte; Großbritannien; DETENTE; UNITED KINGDOM; EAST-WEST RELATIONS; Since 1945; Foreign relations; Great Britain